Environmental Education: Awareness, Urgency and Solutions Through the Bridge of Environmental Fiqh and Green Constitution - Baskoro, Aji (Proceeding International Conference on Religion, Science and Education, 2025)
The Earth faces an environmental crisis that impacts many aspects of life. Climate change, pollution and biodiversity loss are urging the world to take immediate action. Indonesia, as an archipelago with rich biodiversity, is no exception to these challenges. Environmental degradation is caused not only by natural factors but also by humans. Activities exploit nature excessively, indicating a lack of awareness about environmental preservation. Education, as a fundamental tool for imparting knowledge and awareness, must address these challenges. Environmental education is crucial, not only for raising public awareness but also for shaping proactive attitudes and behaviors in safeguarding nature. This paper will explore how the lens of environmental fiqh, grounded in religious values, can collaborate with constitutional principles to establish an environmentally conscious education system. Through a statutory and conceptual approach with qualitative analysis based on literature and using a normative methodology, this study concludes that the perspectives of environmental fiqh and the Indonesian constitution provide ethical and legal foundations for environmental education. Environmental fiqh emphasizes human responsibility as khalifah of the Earth, requiring the awareness that preserving the environment is part of worship and moral duty. In the context of education, environmental fiqh promotes teaching ecological values based on religious principles, including amar ma’ruf nahi munkar. Meanwhile, the Indonesian constitution, particularly Article 28H (1) of the 1945 (Green Constitution), asserts the right of every citizen to a good and healthy environment. This shows that environmental preservation is a shared responsibility, not just of individuals but also of the state. Therefore, environmental education must be integrated into school curricula as part of the state's effort to fulfill constitutional rights. Integrating religious concepts into environmental education enhances not only scientific ecological awareness but also imbues it with a strong spiritual and ethical dimension, creating a society more attuned to the preservation of nature.